Gut microbiota and metabolites: emerging prospects in the treatment of non-small cell lung cancer - Jiao, Jing-Mian; Liu, Chen-Guang; Zang, Dan; Chen, Jun (Frontiers in Immunology, 2025)
Non-small cell lung cancer (NSCLC) is the most prevalent form of lung cancer, accounting for approximately 85% of all cases, and is associated with a poor prognosis. Despite significant advancements in treatment modalities, therapeutic efficacy remains suboptimal, underscoring the urgent need for novel strategies. In recent years, increasing attention has been directed toward the pivotal role of gut microbiota-host interactions in the treatment of NSCLC. This review systematically examines the influence of current NSCLC therapies on gut microbiota and metabolism, explores the relationship between the microbiome and therapeutic response, and highlights the critical functions of probiotics, microbial metabolites, fecal microbiota transplantation (FMT), and dietary interventions in NSCLC management. By elucidating the mechanisms through which gut microbiota and their metabolites modulate treatment efficacy, we investigate the potential of exogenous interventions targeting the gut ecosystem to enhance therapeutic outcomes and mitigate adverse effects. Modulating the intestinal microbiota represents a promising clinical avenue and offers a new frontier for the development of future NSCLC treatment strategies.